Depiction of Lakulisa - Temples of India Project Team (Jio Institute, 2024)
Lakulisa is depicted two-armed and in padmasana (lotus pose) with his hands forming the dhyanmudra (the hand seal gesture for mediation), carrying a lakuta (club), in his left hand and a fruit in his right hand.